Lurking Lima Bean - McGee, Joe; Skaffa, Teo (New York Aladdin, 2021)
Wolver Hollow is not a normal town. The adults are too busy shuffling off to work at the old coffin factory to notice or care, but the kids know all about monsters, ghosts, and strange lights in the sky. Strange things happen in Wolver Hollow. Creepy things. Madeline Harper does not like lima beans and she's not afraid to make that clear. But when she gets sent to bed for not eating her vegetables, she'll find something far worse than her mother's frustration. A lima bean scorned is a terrible thing and it will not stop until Madeline Harper eats her vegetables!
Ages 7-10.
112420
Keywords: Zombies -- Juvenile fiction; Lima bean -- Juvenile fiction; Cities and towns; Humorous stories; Horror tales; Mystery and detective stories; Cooking & Food; Children's stories; Detective and mystery fiction; Fiction; Horror fiction; Juvenile works; Mystery fiction